Arfs on the Golgi: four conductors, one orchestra - Dejgaard, Selma Yilmaz; Presley, John F. (Frontiers in Molecular Biosciences, 2025)
Arfs are small Ras-superfamily proteins important for regulating membrane trafficking including the recruitment of vesicular coats as well as a diverse range of other functions. There are five Arfs in humans: two Class I Arfs (Arf1 and Arf3), two Class II Arfs (Arf4 and Arf5) and one Class III Arf (Arf6), with Class I and Class II Arfs present on the Golgi apparatus among other locations. These Golgi Arfs (Arf1, Arf3, Arf4 and Arf5) are highly similar in sequence, and knockout studies have established a complex pattern of redundancy, with Arf4 alone able to support cell survival in tissue culture. Moreover, adding to the complexity, functions of Arfs on distinct membranes can involve non-overlapping sets of effectors (e.g., COPI on cis-Golgi membranes and clathrin adaptors on trans-Golgi network). The three classes of Arfs are found in most metazoans, suggesting biologically important specialization the details of which are beginning to emerge. This review examines recent studies using siRNA and CRISPR/Cas9 knockouts of mammalian Arfs combined with functional assays of the secretory pathway in the context of detailed localization of fluorescently-tagged Arfs by fluorescent and super-resolution microscopy and the existing literature using more conventional techniques. We suggest that specificity of effector recruitment involves additional membrane determinants which need to be considered in future studies.